(untitled) (Research, Society and Development, 2021)
Women’s football has conquered space on the world stage in recent years, given the increase in the number of players, spectators as well as the increase in the transmission of games on TV channels. In Brazil, this is no different, with the Brazilian championship as the main competition in the modality. When it comes to soccer, the goal is the main moment of the sport, and it can occur from normal attacks or counter-attack plays, from set pieces or from technical failures. In this sense, the objective of this study was to classify the goals that happened in the Brazilian women’s soccer championship in 2020, within the variables, attacking plays, counterattacks, set pieces and technical failures through the analysis of compact videos of the best moments of the games. The study included a total sample of 134 games in the 2020 Brazilian women’s soccer championship played by 16 clubs. The analysis was performed using the scout method. It was possible to conclude that most of the goals in the championship occurred in attack plays or set pieces. The work observed the strengths and shortcomings of each team regarding the plays that give rise to the goals.